(untitled) (Research, Society and Development, 2022)
A retrospective epidemiological analysis of 52 patient´s records of patients under 55 years of age, admitted to the Hospital São Lucas de Cascavel (PR), with a diagnosis of stroke carried out. The main type of stroke observed in this population was hemorrhagic stroke (HCV), occurring in 88.4% of the cases, while ischemic stroke was observed in 11.6% of the cases. Among the main risk factors analyzed in these patients, arterial hypertension was the main one, being present in 84.9% of the strokes. In addition to hypertension, other important risk factors were also observed, such as smoking, alcoholism, dyslipidemia, diabetes mellitus and traumatic brain injury. Thus, it is noted that in this study group, the potentially modifiable and controllable risk factors are prevalent, suggesting a greater need for incentives for prevention campaigns and early detection of risks directed at the young population.